Adolf Weber statt Freiburger Schule? Die theoretischen Ansichten über Geldpolitik in der frühen Bundesbank am Beispiel von Bernhard Benning - Jan Greitens (IBF - Institut für Bank- und Finanzgeschichte e.V., 2022)
– This paper analyses the early years of the history of the Bundesbank from a history of economic thought-perspective. The study uses the example of Bernhard Benning, who was heading the Economics Department of the Reichs-Kredit-Gesellschaft, one major banks owned by the German Reich during the National Socialist era. After the war Benning became a member of the Executive Board of the Deutsche Bundesbank for 22 years. Benning was a student of Adolf Weber and was strongly influenced by the latter`s opportunistic, conservative, and pro-business liberalism, rather than by ordoliberal ideas. Benning drew his legitimacy for his role in the early Federal Republic from his public criticism of war financing and from warning against inflation in the DonnerBenning Debate since 1942/43. In this tradition, the early Bundesbank was Weberian rather than ordoliberal, so fixed exchange rates were favored, and a strong business and investment perspective was adopted.
Keywords: B26; B31; E58; N14; N24; 330; Bundesbank; Reichs-Kredit-Gesellschaft; Adolf Weber; Ordoliberalism; National Socialism; Money; Inflation